Principles of mobile communication / Gordon L. Stüber. - Stüber, Gordon L., 1958- (Springer, 2017)
This book's mathematically rigorous coverage of physical layer wireless communications is now in a third, fully revised and updated edition. As well as dealing with core principles, it explains the finer details essential for in-depth research on the topic.